2021
DOI: 10.1021/acs.jmedchem.1c00141
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bisubstrate Inhibitors for Protein N-Terminal Acetyltransferase D

Abstract: Protein N-terminal acetyltransferase D (NatD, NAA40) that specifically acetylates the alpha-N-terminus of histone H4 and H2A has been implicated in various diseases, but no inhibitor has been reported for this important enzyme. Based on the acetyl transfer mechanism of NatD, we designed and prepared a series of highly potent NatD bisubstrate inhibitors by covalently linking coenzyme A to different peptide substrates via an acetyl or propionyl spacer. The most potent bisubstrate inhibitor displayed an apparent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The level of product formation for actylation of MDEL 24 , DDDI 24 and EEEI 24 was determined to be 119 ± 5.61 μM, 50.5 ± 1.0 μM, and 42.4 ± 0.95 μM, respectively ( Goris et al, 2018 ). In our inhibitor design, we decided to continue using a tetrapeptide for the protein-mimicking part as previous studies have shown that these are the most important residues for inhibitory activity ( Liszczak et al, 2011 ; Foyn et al, 2013 ; Liszczak et al, 2013 ; Støve et al, 2016 ; Hong et al, 2017 ; Goris et al, 2018 ; Deng et al, 2020 ; Deng et al, 2021 ; Deng et al, 2023 ). Co-crystal structures of NAT-bisubstrate inhibitor complexes typically show that these four amino acids are most important for protein-inhibitor binding interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of product formation for actylation of MDEL 24 , DDDI 24 and EEEI 24 was determined to be 119 ± 5.61 μM, 50.5 ± 1.0 μM, and 42.4 ± 0.95 μM, respectively ( Goris et al, 2018 ). In our inhibitor design, we decided to continue using a tetrapeptide for the protein-mimicking part as previous studies have shown that these are the most important residues for inhibitory activity ( Liszczak et al, 2011 ; Foyn et al, 2013 ; Liszczak et al, 2013 ; Støve et al, 2016 ; Hong et al, 2017 ; Goris et al, 2018 ; Deng et al, 2020 ; Deng et al, 2021 ; Deng et al, 2023 ). Co-crystal structures of NAT-bisubstrate inhibitor complexes typically show that these four amino acids are most important for protein-inhibitor binding interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The first catalytic mechanism of a human NAT ( Evjenth et al, 2012 ), as well as the first structures of a NAT and NAT-complex bound to its peptide substrate, have been presented ( Liszczak et al, 2011 ; Liszczak et al, 2013 ; Støve et al, 2016 ). Taking advantage of this information, we and others have developed peptidic NAT inhibitors that are based on covalently linking mimics of the two substrates of the biochemical reaction, i.e., coenzyme A (CoA) and a short peptide carrying an N-terminal bromoacetyl group ( Figure 1 ) giving a thioether-linked acetyl moiety ( Foyn et al, 2013 ; Støve et al, 2016 ; Goris et al, 2018 ; Deng et al, 2021 ). In these studies it has been found that it is sufficient to use the four amino acids from the N-terminus of the protein substrates to obtain potent bisubstrate inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some inhibitors have been reported for this important acetyltransferase. 42 , 43 Given that NatD promotes breast cancer cell metastasis, NatD enzymatic inhibition may provide an epigenetic therapeutic strategy for breast cancer. In the current study, we show that FOXA2 acts as a key factor mediating the function of NatD and MMP14 in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The competitive inhibition study was performed using a previously described fluorescence assay. 38 hNatD activity was measured at 25 °C under the following conditions in a final reaction volume of 40 μL: 50 nM hNatD, 15 μM ThioGlo4, 0.6 μM AcCoA, and 6 μM H4-5 in reaction buffer (25 mM HEPES, 150 mM NaCl, 0.01% (v/v) Triton, pH 7.5). The 10X concentration of mutant or modified peptides was diluted with reaction buffer and then 3-fold serially diluted with reaction buffer.…”
Section: ■ Methodsmentioning
confidence: 99%